Comparison of Misoprostol and Manual Vacuum Aspirator for Managing Early Pregnancy Miscarriage: Managing Early Miscarriage - Pirzada, Hina; Shabbir, Nosheena; saeed, Saima; Anwar, Amina; Khawaja, Uzma; Sarwar, Hina (Pakistan Journal of Health Sciences, 2024)
Manual vacuum aspiration is a safe and effective technology for the treatment of incomplete miscarriage but it is not widely available and affordable in rural areas particularly in low-resource countries. Objective: To compare efficacy, safety and acceptability of misoprostol and manual vacuum aspirator in management of early pregnancy miscarriage Methods: Prospective quasi experimental study Department of gynecology and obstetrics, Sheikh Khalifa Bin Zayed Al Nahyan (CMH).Muzaffar Abad. Study duration was 6 months. A sample of 90 women was calculated using WHO calculator. Patients were approached through non probability consecutive sampling. After following inclusion and exclusion criteria, Patients were randomly divide into two groups; Group A was given misoprostol while group B was patients underwent manual vacuum aspiration. Data were analyzed with SPSS version 25.0. Chi-square and fissure exact test was applied. Results: Total 90 patients were included in study. Mean age of patients was 35.4 ± 3.2SD. Treatment failure/incomplete uterine evacuation was significantly lower in manual vacuum aspiration group as compared to misoprostol group (45.6% vs 36.7%, p=0.05). Misoprostol showed less adverse events (p=0.03) and high satisfaction rate (p=0.00) as compared to manual vacuum aspirator. Conclusions: Manual vacuum aspirator is more effective in complete uterine evacuation as compared to misoprostol. However, misoprostol is found as more safe with limited side effects and highly acceptable drug as compared to manual vacuum aspirator. It is recommended to use misoprostol as a better choice for management of early pregnancy loss in resource limited areas